Pembelajaran Keagamaan Pendidikan Agama Islam Anak Berkebutuhan Khusus - Mahsa Razi Al Afghan; Moch. Tolchah; Din M. Zakariya (Dinasti Review, 2024)
This study deals with the learning of Islamic Education for Children with Special Needs (ABK) which can be affirmed that education is the capital and basic human needs in order to realize its rights and duties as an individual, as a member of the community and as a being of God Subhanahu wa Ta’ala and also affirms that the education is a human right. Therefore, in achieving the process of realization of the basic rights in education, it is necessary to ensure that all children's rights in the field of education must be realized, a quality education strategy and administration is required. This research uses a library method with a qualitative research approach. The results of the research showed the need for strong and positive support in the creation of effective learning models in their application especially for children with special needs.